2010
DOI: 10.1002/elps.201000274
|View full text |Cite
|
Sign up to set email alerts
|

Identification of poliovirions and subviral particles by capillary electrophoresis

Abstract: Poliovirions, purified from infected cell extracts with anion-exchange chromatography, can be analyzed and identified by CE in untreated fused silica capillaries using UV detection. Other subviral particles can be eluted as well from the same infected cell extract using a higher salt concentration buffer on the ion-exchange chromatography. Virions can be identified because of their conversion into empty capsids upon heating at 561C. As a result of heating, the viral genome is released from the capsid. Here, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…Capillary electrophoresis was used to quantitate the poliovirus particles (Oita et al, 2011), and to distinguish the D-antigen from the heat denaturated poliovirus, non-exposing the D-antigen (Halewyck et al, 2010). Additionally, Okun et al (2000) demonstrated that another picornavirus, the human rhinovirus, was still viable after a similar capillary electrophoresis procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Capillary electrophoresis was used to quantitate the poliovirus particles (Oita et al, 2011), and to distinguish the D-antigen from the heat denaturated poliovirus, non-exposing the D-antigen (Halewyck et al, 2010). Additionally, Okun et al (2000) demonstrated that another picornavirus, the human rhinovirus, was still viable after a similar capillary electrophoresis procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to real life virological samples, this is still a high concentration, and it was expected that this method will not be useful to study PV from cell extracts, where much lower concentrations may occur. Also, when highly concentrated PV samples are degraded upon heating, or viral-assembly particles are injected, the low level of the signal will make the investigation of those sub-viral particles extremely difficult [33]. Therefore a signal-increasing approach, also applicable to less pure PV samples, was necessary as an elegant solution to the problems mentioned above.…”
Section: Preliminary Investigationsmentioning
confidence: 97%
“…1A trace (a)). The use of SGPV samples for method development was necessary to simplify the peak identification, which is difficult in the absence of reference materials for PV [33]. However, for this method, the possible applications are limited to PV identification and quantification, after extensive purification of the original samples.…”
Section: Preliminary Investigationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Composition of the BGE and parameters such as temperature, voltage, and injection conditions were varied (see Table 1 for the conditions used in this and in the following papers). The same analysis conditions, including SDS as additive, as in [8], were used in a subsequent paper [9], and subviral particles obtained by incubation at 561C were separated and identified. Furthermore, these authors achieved separation of the viral genomic RNA, empty capsids, and a not further characterized ''ribonucleoprotein.''…”
Section: Virusesmentioning
confidence: 99%